PERSEPSI MASYARAKAT TERHADAP PENGEMBANGAN EKOWISATA BUKIT SITETEPAN (Studi Kasus Desa Tegalsari, Kecamatan Bruno, Kabupaten Purworejo) - Mustika, Delima Canda; Lestari, Eny; Sugihardjo, Sugihardjo (AGRITEXTS: Journal of Agricultural Extension, 2019)
The Tegalsari village is the large village with the second largest population in Bruno District, Purworejo Regency. It makes Tegalsari village have several potentiality to become ecotourism place. The government wants to develop ecotourism in Tegalsari Village to boost the economy and the welfare condition that categorized as poor village. The first stage of ecotourism development is planning stage to know the public perception of the development of ecotourism in Tegalsari Village.This research aims to examine public perceptions of the development plan of Tegalsari Village ecotourism, Bruno District, Purworejo Regency. This research uses qualitative basic methods with interactive inductive data analysis methods. The research location was chosen intentionally or purposively. Determination of informants in this study using the snowball sampling technique. The number of informants is 14 informants. The validity of the data is obtained using data triangulation. The results of this study indicate that the community provides a positive perception of ecotourism development. Ecotourism development was initiated and welcomed by the local community. The community hopes that Bukit Sitetepan ecotourism development can improve people’s welfare. There are several supporting factors and obstacles to the process of developing ecotourism and ecotourism development also bring positive and negative impacts. According to the community, the positive impact caused is greater than the negative impact.